EDUCATIONAL MANAGEMENT IN THE DIGITAL ERA: THE ROLE OF TECHNOLOGY-BASED PEDAGOGY IN IMPROVING THE QUALITY OF LEARNING - Br Ginting, Nurcitra Rehulina; Astra, I Made; Dwi Atmanto (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Rapid development of digital technology has brought fundamental changes in the global education system which triggered a paradigm shift from traditional teaching methods to more innovative and learner-centered approaches. This study aims to explore how technology-based pedagogy can improve the quality of learning in the digital era and its implications for education management. Through a qualitative literature study, this study analyzes various scientific sources in the last decade to identify best practices in the integration of educational technology. The results of the study indicate that the application of digital pedagogy can create an interactive, inclusive, and adaptive learning environment. However, its implementation still faces challenges such as the digital access gap, limited infrastructure, and low digital literacy of teachers. Therefore, strategic efforts are needed to improve educator competence, design digital curriculum, and strengthen education management that supports comprehensive digital transformation. The application of digital pedagogy has been proven to improve the quality of learning by providing an interactive learning environment that supports the development of 21st century skills and expands access to learning resources. This study concludes that technology-based pedagogy plays an important role in improving the quality of learning and supporting adaptive education management in the digital era.